HOW TO INCREASE JOB SATISFACTION AND ORGANISATIONAL COMMITMENT IN THE ICT SECTOR THROUGH JOB DESIGN - Bogićević Milikić, Biljana; Čučković, Milica (Economic Annals, 2019)
The paper investigates the relationship between job design and work-related attitudes (job satisfaction and organisational commitment) in the Infor-mation and Communication Technology (ICT) sector. We use data collected via an online questionnaire (using the Google Forms platform) from 97 employees work-ing in the ICT sector in Serbia. The data was collected between February and June 2019. The analysis shows that job design is a predictor of both job satisfaction and organisational commitment. Of the five investigated job dimensions (Skill variety, Task identity, Task significance, Autonomy, Feedback from job), ‘Autonomy’ was the most positively associated with job satisfac-tion (r=0.629) but was only moderately as-sociated with organisational commitment (r=0.4). The other job dimensions were found to be weakly correlated with the in-vestigated work attitudes, although the re-lationships were positive. Furthermore, the results indicate that work engagement me-diates both investigated relationships, pro-viding a deeper insight into how job design is translated into positive work-related at-titudes. We discuss the possible managerial implications of the ‘Autonomy’ dimension and the interventions in work engagement required to positively influence work-relat-ed attitude formation and management in the ICT sector, and we distinguish between ‘ bottom-up’ and ‘top-down’ interventions.